Identification of plant semiochemicals and evaluation of their interactions with early spring insect pests of asparagus. Issue 1 (1st January 2016) - Morrison, William R.; Ingrao, Adam; Ali, Jared; Szendrei, Zsofia
ABSTRACT: Information is lacking on the chemical ecology of asparagus, and knowledge about the effects of its volatile emissions on its associated early season pest species is completely absent. The current study aimed to (1) evaluate whether the asparagus miner responds to asparagus volatiles, (2) identify and compare the changes in asparagus host plant volatiles from mechanical and chewing damage by the black cutworm, a temporally co-occurring species with the asparagus miner, and (3) assess how asparagus volatiles affect asparagus miner populations in the field. Results indicated that asparagus miners were significantly attracted to healthy asparagus stems when compared to clean air. Damaged asparagus headspace volatiles were quantitatively and qualitatively different from healthy plants. Volatile baits elicited a range of responses, but their effects were inconsistent between sampling years and phenology-dependent. Overall, we demonstrated that the chemical ecology of asparagus may be altered by its pest community, and volatiles identified from asparagus may impact the behavior of the asparagus miner.